Answer:
B 41.4
Step-by-step explanation:
complete Pythagoras for general triangles :
c² = a² + b² - 2ab×cos(C)
with "c" being the side opposite of the angle C.
=>
8² = 10² + 12² - 2×10×12×cos(C)
64 = 244 - 240×cos(C)
240×cos(C) = 244 - 64 = 180
cos(C) = 180/240 = 18/24 = 3/4 = 0.75
C = 41.40962211... ≈ 41.4
Step-by-step explanation:
Hey there!
Please see your required answer in picture.
<u>Hope</u><u> it</u><u> helps</u><u>!</u>
Answer:
Step-by-step explanation:
-11x² + 2x = 10
-11x² + 2x - 10 = 10 - 10
-11x² + 2x - 10 = 0
x = <u>-(2) +/- √((2)² - 4(-11)(-10))</u>
2(-11)
x = <u>-2 +/- √(4 - 440)</u>
-22
x = <u>-2 +/- √(-436)
</u> -22<u>
</u>x = <u>-2 +/- 2i√(109)
</u> -22
x = <u>-2 + 2i√(109</u>) x = <u>-2 - 2i√(109)</u>
-22 -22
x = ¹/₁₁ - ¹/₁₁i√(109) x = ¹/₁₁ + ¹/₁₁i√(109)
<u />